Push-out tests on bolted shear connectors in composite cold-formed steel beams. (July 2021) - Hosseinpour, Mahmoud; Zeynalian, Mehran; Ataei, Abdoreza; Daei, Maryam
Abstract: Composite beams comprised of steel sections and concrete slabs, are one of the most widely used beams due to their advantages such as improving stiffness and strength compared to bare steel or reinforced concrete beams. Moreover, another important advantage of such beams is to prevent buckling of steel section by placing it under tension, which is especially important for low-thickness steel sections such as cold-formed steel (CFS) sections. Although the use of CFS sections in combination with concrete slabs can increase the efficiency of such sections, their low thickness makes it difficult to weld traditional studs as shear connectors on their top flanges. The current paper presents an experimental investigation about the behavior of bolted shear connectors in the composite cold-formed steel beams as a suitable alternative to welded shear studs. To do so, three main parameters including thickness of CFS sections, and size and strength of bolts were taken into account. Fifteen full-scale push-out specimens were constructed and tested. The ultimate load, ductility, stiffness and failure mode of all specimens were then assessed; and their results were reported and precisely discussed. Based on the results, depending on the size and strength of bolts, the ultimate load per shear connector for 1 mm thick CFS sections' specimens is found between 6.2 and 8.6 KN, while this value for specimens by 2 mm thick CFS sections, is found between 15.6 and 26.8 KN. Moreover, based on EC4, the ductility of shear connectors was examined; the results indicate that all bolted shear connectors in this study can be assumed ductile and can be used in partial shear connections. Highlights: Structural performance of CFS-concrete composite beams is investigated. 15 full scale push-out tests are conducted. The failure modes, ductility and stiffness of the composite sections are studied. Thickness of CFS sections, size and strength of bolts were taken into account.